COMPARISON OF CHILDREN AND ADULTS WITH TUBERCULOUS MENINGITIS IN ELAZIG, TURKEY - GOKCE, C; KIHC, SS; MUNGEN, B; ARISOY, ES; ARISOY, AE; GUVENC, HY; BEKTAS, S (Oxford Univ Press, 1992)
Retrospective evaluation of 16 cases of tuberculous meningitis revealed that BCG vaccination and tuberculin positivity were rare in pediatric as well as adult patients. Children with disease had developmental retardation and a high rate of maternal illiteracy as compared to normal controls.
Keywords: Bcg Vaccination